2022
DOI: 10.1002/jqs.3454
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of a large proglacial lake in the Rostov‐Kostroma lowland, north‐central European Russia

Abstract: The Rostov-Kostroma lowland is a depression stretched between the end-moraine ridges of the Moscovian (MIS 6) glaciation crossed by the Upper Volga River. According to the theory accepted since the 1970s, in the Last Glacial epoch (MIS 2) this lowland was occupied by a glacially dammed lake that drained about 15 000 years ago, allowing the modern river system of the Upper Volga to appear. In this study, we test this concept using a synthesis of previously published data and new data on geomorphology, structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Given the small size of the SD Lake, the lack of evidence of its overflow outside of the Severnaya Dvina valley, and all signs of flow persistence in the Vychegda River system, this scenario seems unrealistic. It also contradicts other geological and geomorphological data on the absence of overflows through the watershed into the Volga basin (Panin et al, 2020;Borisova et al, 2022) and the absence of traces of massive glacial runoff in the upper Volga (Panin et al, 2021).…”
Section: Sis Maximum Age and Extent And Drainage Reorganization In Th...contrasting
confidence: 75%
“…Given the small size of the SD Lake, the lack of evidence of its overflow outside of the Severnaya Dvina valley, and all signs of flow persistence in the Vychegda River system, this scenario seems unrealistic. It also contradicts other geological and geomorphological data on the absence of overflows through the watershed into the Volga basin (Panin et al, 2020;Borisova et al, 2022) and the absence of traces of massive glacial runoff in the upper Volga (Panin et al, 2021).…”
Section: Sis Maximum Age and Extent And Drainage Reorganization In Th...contrasting
confidence: 75%
“…Also, a number of recent studies (Panin et al, 2020(Panin et al, , 2022Borisova et al, 2022) showed that neither the proglacial lakes in the upper Volga region proposed by Kvasov (1979), nor the overflow to the Volga River from the Arctic basin occurred in MIS 2.…”
mentioning
confidence: 97%